Dialysis access : current practice - Akoh, J. A. (Jacob A.); Hakim, Nadey S., 1958- (Imperial College Press ; Distributed by World Scientific Pub. Co., 2001)
The incidence of treated end stage renal disease (ESRD) continues to rise, particularly in the western world. Although renal transplantation is the treatment of choice for ESRD, the decline in the number of cadaveric organs, coupled with the rising demand for transplantation, means that an increasing number of patients will have to depend on dialysis. Vascular or peritoneal access is the Achilles' heel of any dialysis service. This book offers a clear description of the state of the art in providing and preserving a durable and reliable access. It also points the way to dialysis in the 21st ce.